2021
DOI: 10.1186/s12985-021-01699-6
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of the chest CT score in COVID-19 patients: a cross-sectional study

Abstract: Background Since the COVID-19 outbreak, pulmonary involvement was one of the most significant concerns in assessing patients. In the current study, we evaluated patient’s signs, symptoms, and laboratory data on the first visit to predict the severity of pulmonary involvement and their outcome regarding their initial findings. Methods All referred patients to the COVID-19 clinic of a tertiary referral university hospital were evaluated from April to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…At the group level, lesion burden was consistently seen to be considerably greater in severe type patients than in common type patients when four evaluation techniques were used. It was established that both semiquantitative and quantitative approaches had great repeatability when evaluating inflammatory lesions and are capable of distinguishing between patients with the common type and those with the severe type [ 13 , 14 ]. The severity of the initial disease was associated with residual lung changes in 42% of discharged COVID-19 patients included in a mid-term follow-up study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the group level, lesion burden was consistently seen to be considerably greater in severe type patients than in common type patients when four evaluation techniques were used. It was established that both semiquantitative and quantitative approaches had great repeatability when evaluating inflammatory lesions and are capable of distinguishing between patients with the common type and those with the severe type [ 13 , 14 ]. The severity of the initial disease was associated with residual lung changes in 42% of discharged COVID-19 patients included in a mid-term follow-up study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, as the lung CT score increased, the presence and the severity of the neurologic disorders increased. In the study of Yazdi et al [22], lung CT scores were The other limitation of this study is that neurological disorders were not handled and evaluated separately.…”
Section: Discussionmentioning
confidence: 96%
“…In the literature, to our knowledge, few studies evaluated the clinical and laboratory parameters that can predict a worse CT score at admission [18] , [19] , [20] , [21] . The study by Francone et al, including 130 symptomatic COVID-19 patients showed that the Pan CT score was significantly correlated with C-reaction protein (CRP) (p < 0.0001) and D -dimer (p < 0.0001) levels [18] .…”
Section: Discussionmentioning
confidence: 99%
“…The study by Francone et al, including 130 symptomatic COVID-19 patients showed that the Pan CT score was significantly correlated with C-reaction protein (CRP) (p < 0.0001) and D -dimer (p < 0.0001) levels [18] . The paper by Yadzi et al [19] is the largest study, to our knowledge, including 478 participants, that evaluated the impact of different laboratory, clinical and demographic parameters to predict a CT score, with a score 0–25 based, similar to the Pan score. They found that anosmia, respiratory rate, CRP (with a cut-off of 90), WBC (with a cut-off of 10.000) and SpO2 (with a cut-off point of 93) was associated with a higher chest CT score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation